Clinical and demographic study of microsporidial keratoconjunctivitis in South India: a 3-year study (2013–2015). Issue 10 (22nd February 2017) - Agashe, Rohan; Radhakrishnan, Naveen; Pradhan, Sayali; Srinivasan, Muthiah; Prajna, Venkatesh N; Lalitha, Prajna
Abstract : Aim: To study the demographic profile, clinical features, treatment outcome and ocular morbidity of smear-positive microsporidial keratoconjunctivitis. Methods: Retrospective case series of all patients with clinical features of microsporidial keratoconjunctivitis and who were smear positive for the same on Gram stain from January 2013 to December 2015. Demographic data, predisposing factors, microbiological investigations, clinical course and visual outcome were analysed. Results: Of the 10 655 patients with conjunctivitis, 550 (5.2%) patients were positive for microsporidia on Gram stain during this time period. The disease was prevalent throughout the year with an increased incidence from July to December. Bilateral involvement was seen in 27 (4.9%) patients. There was no predisposing risk factor in 428 (77.8%) patients. 384 (69.1%) patients had received prior treatment before presentation to us with the most common drug being antibiotic in 285 (49.4%) patients. All the patients underwent diagnostic corneal debridement and received topical 0.3% fluconazole eye drops four times a day. Of the 296 patients who followed-up, 187 (63.1%) patients had complete resolution without sequelae. 68 (22.9%) had persistent superficial punctate keratopathy, 30 (10.1%) developed subepithelial nummular keratitis. No significant change in visual acuity was seen in 255 (80.7%) eyes, two or more line improvement was seen in 48 (15.2%) eyes, while two or more line worsening was seen in 13 (4.1%) eyes. Conclusions: Microsporidial keratoconjunctivitis is prevalent in South India throughout the year. The characteristic clinical signs and simple microbiological investigation help us to differentiate it from adenoviral keratoconjunctivitis. The visual prognosis is good.